Efficacy of Transistor Interleaving in DICE Flip-Flops at a 22 nm FD SOI Technology Node - Christopher J. Elash (Applied Sciences, 2022)
Fully Depleted Silicon on Insulator (FD SOI) technology nodes provide better resistance to single event upsets than comparable bulk technologies, but upsets are still likely to occur at nano-scale feature sizes, and additional hardening techniques should be explored. Three flip-flop designs were implemented using Dual Interlocked Cell (DICE) latches in a 22 m FD SOI technology node. Additional hardening was implemented in the layout of each design by using transistor spacing and interleaving. Comparisons were made between a standard DICE design and two other designs making use of the new Continuous Active (CnRx) Diffusion construct and guard-gate transistor stacking through alpha particle and heavy ion irradiation. Designs making use of the CnRx construct for performance improvements were more likely to experience upsets due to higher collected charges in the increased diffusion regions. Conversely, transistor stacking showed strong soft error rate resilience because of the natural isolation between transistors in the FD SOI technology. Overall, the efficacy of transistor interleaving in flip-flops using DICE latches was found to be extremely robust in the 22 nm FD SOI technology node.